SURFACE POLLEN DEPOSITION ON GLACIER FORELANDS IN SOUTHERN NORWAY I: LOCAL PATTERNS OF REPRESENTATION AND SOURCE AREA AT STORBREEN, JOTUNHEIMEN - Pardoe H.S. (My University, 2006)
The relationship between vegetation and surface pollen deposition is examined at Storbreen glacier foreland where a clear plant succession exists. The aim is to determine whether the distinct plant communities present produce characteristic pollen assemblages. The influence of environmental factors is also considered. Pollen assemblages from moss polsters, collected from 22 paired sampling sites across the foreland, are compared with local vegetation. Two-way indicator species analysis and detrended correspondence analysis are employed to identify clusters and sequences, initially in the vegetation data and subsequently in the pollen data sets. Vegetation and pollen data are compared simultaneously using canonical correspondence analysis. Three main plant communities are distinguished: pioneer, heath and snowbed. Broadly, each community produces characteristic pollen assemblages. Boundaries between groups are not clear-cut, reflecting the mosaic of plant communities present. Recognition of distinct plant communities is hampered by the prevalence of long-distance arboreal pollen and poor representation of entomophillously pollinated taxa. Late in the succession up to 78% of pollen could originate locally. Use of the non-arboreal pollen sum significantly improves correspondence with vegetation. The importance of indicator taxa is considered and both Salix and Empetrum are found to distinguish successfully early phases of succession from later phases. Strong correlations exist between the primary ordination axes of vegetation and pollen and with terrain age and altitude (for example, the correlation between altitude and total land pollen Axis 1 is r= -0.76). The surface data add new information to the interpretation of tree colonization in the area during the Holocene.
Keywords: SURFACE POLLEN; POLLEN REPRESENTATION; PLANT SUCCESSION; CLASSIFICATION AND ORDINATION; RELEVANT SOURCE AREA OF POLLEN; MOSS POLSTER; GLACIER FORELAND; JOTUNHEIMEN; NORWAY; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен